SANTRIPRENEURSHIP: INCREASING ECONOMIC INDEPENDENCE THROUGH ENTREPRENEURSHIP CHARACTER EDUCATION AT THE UMMUL AYMAN ISLAMIC BOARDING SCHOOL SAMALANGA - Rahmati, Arinal; Salman, Salman; Januddin, Januddin; Mulyadi, Deni; Mubarak, Fadhil (Jurnal As-Salam, 2023)
Islamic boarding schools began to transform into entrepreneurship activities, including the Ummul Ayman Islamic boarding school located in Samalanga, Bireuen district, which began to promote economic independence through the pesantrenpreneur. This initiative was motivated by the high percentage of students whose costs were borne by the foundation and the council of dayah teachers who were not yet financially independent and did not have specific skills to support the economy. This study aims to describe the business unit model developed based on a pesantrenpreneur, strategies for developing an interest in becoming an entrepreneur, and any obstacles experienced by the Ummul Ayman Islamic boarding school in applying entrepreneurship. The method used is a case study by collecting data through in-depth interviews, which are analyzed using a qualitative approach. The study found four clusters: agriculture, fisheries and animal husbandry, cooperatives, and printing. Meanwhile, the strategy for developing interest is carried out through entrepreneurship education for students starting in junior high school through a training program created at the Islamic boarding school itself. Then, the students are included in programs and seminars in the form of FGDs and TOTs organized by various parties. The recruitment of Islamic boarding school teachers is also one of the strategies for producing students who are interested in entrepreneurship. The constraints are influenced by the narrow space for product marketing, lack of product reliability, and lack of cooperation with various parties, including government assistance.